Advancing the ASEAN economic community: more trade, digitalisation and sustainability - Desker, Barry (2023)
This week’s ASEAN Summit in Phnom Penh will likely highlight three initiatives to push the regional economic agenda forward. The thrust will focus on consolidating gains from facilitating trade, harnessing digitalisation, and embedding sustainability in ASEAN’s economic integration.